STRATEGIC MANAGEMENT FOR INTEGRATION OF ENVIRONMENTAL EDUCATION AND ISLAMIC EDUCATION - Farah Pramudita (Balai Diklat Keagamaan Jakarta, 2023)
Abstract The purpose of this research describes the integration of environmental education and Islamic education through strategic management concepts. Problem research focuses on integrating environmental and Islamic education in Islamic educational institutions. It was conducted in the qualitative method of case studies and analyzing strategic management data using Wheelen and Hunger's theory. The results were divided into four steps to integrate environmental education and Islamic education, which are as follows: 1). Environmental scanning by SWOT (Strengths, Weaknesses, Opportunities, and Threats) matrix; 2). Strategy formulation interprets environmental scanning into mission, objectives, strategies, and policy; 3). Strategy implementation emphasizes programs, budgets, and procedures; 4). Evaluation and control are the performance of teachers' and students' behavior toward the environment; in conclusion, that integration can be shaped if four strategic management steps are run in Islamic educational institution